Kajian Penggunaan Debu Limbah Tembakau dan Pemberian Vermikompos Terhadap Populasi Ditilenchus pada Bawang Merah - Yanuar Mahir Hermawan; Subagiya Subagiya; Ato Sulistyo (Agrotechnology Research Journal, 2017)
Shallot is a high value commodity for Indonesian people. The rate of shallot production is considered quite slow considering of the increasing population, income, and the area of shallot cultivation. On the cultivation of shallots common obstacle of Ditylenchus that cause damage to the stems and shallot bulb. The dust of tobacco and vermicompost waste is known to suppress the development of nematodes. This study aims to examine the use of tobacco ash waste and vermicompost on the population of Ditylenchus nematodes as well as the growth and yield of shallot. This research was conducted at Faculty of Agriculture, Sebelas Maret University (UNS) Surakata in August to December 2016. The study was performed using Completely Randomized Design (CRD) with treatments in the form of tobacco dust, vermicompost, combined tobacco dust and vermicompost and control treatment. Data were analyzed using variance test (F test) with 5% level. If the result shows significant effect then followed by DMRT of 5% level. The result of this research showed that the use of combination of tobacco ash waste and vermicompost could decrease nematode ditylenchus population in the soil. The use of tobacco ash waste could decrease total of parasite nematode population on plant tissue. The treatment didn’t give any effect to shallot’s yield. Shallot’s yield was not influenced by the existence of nematode ditylenchus and another on plant tissue.